Pengaruh Lama Fermentasi Terhadap Kualitas Mutu Pickle Mentimun - Karlyle Rymulan Parhusip; Marisa Sitanggang; Siska Benecdita Siahaan; Yefta Darniati Sinaga; Yokhe Maria Anastasya Tampubolon; Ahmad Shafwan S Pulungan; Adelia Febriyossa (CV.ITTC INDONESIA, 2025)
This study aimed to determine the effect of fermentation duration on the quality of cucumber pickles (Cucumis sativus L.). Cucumber pickles are fermented products involving lactic acid bacteria (LAB) activity, which enhances sensory attributes and nutritional value. A descriptive method was employed using three fermentation durations: 3, 5, and 7 days. Observed parameters included pH changes, color variation, and organoleptic tests (appearance, aroma, taste, texture, and flavor balance). The results indicated that 5-day fermentation provided the best overall quality, particularly in aroma, taste, and flavor balance, while 3-day fermentation showed better appearance and texture. Conversely, 7-day fermentation significantly reduced organoleptic quality. The study concluded that fermentation time significantly affects pickle quality, with the optimal fermentation period occurring on the fifth day.